2015
DOI: 10.5539/ijbm.v10n10p216
|View full text |Cite
|
Sign up to set email alerts
|

Board Composition and Companies’ Performance: Does Political Affiliation Moderate the Relationship?

Abstract: Board composition is one of the distinct characteristics of Governance that is believed to contribute significantly to firm value. This study examines the impact of board composition, presence of nomination, audit and remuneration committees on companies' performance. Additionally, the moderating effects of political affiliation on the relationship between board composition and companies' performance is also tested. A sample size of 2280 companies from Bursa Malaysia for the period 2010 to 2012 is used. Hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 133 publications
0
7
0
Order By: Relevance
“…These indicators would be: Tobin's Q, price-to-book ratio-PBR, Return on capital employed-ROCE, Return on own-funds -ROE and ROI. Relevant measures were used for the politic experience (Leong et al, 2015), strategic experience (Lambert and Ghaya, 2016), demographic variables (Muller, 2014), structural variables (Arora and Sharma, 2016) and control variables (Terjesen et al, 2015). The study variables were chosen from previous studies by characterizing them in terms of availability and measurement.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These indicators would be: Tobin's Q, price-to-book ratio-PBR, Return on capital employed-ROCE, Return on own-funds -ROE and ROI. Relevant measures were used for the politic experience (Leong et al, 2015), strategic experience (Lambert and Ghaya, 2016), demographic variables (Muller, 2014), structural variables (Arora and Sharma, 2016) and control variables (Terjesen et al, 2015). The study variables were chosen from previous studies by characterizing them in terms of availability and measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, Dou et al (2015) show that firms with government-owned managers have a significantly lower return on assets ROA than those with no political linkage, particularly in non-regulated industries (Leong et al, 2015). This negative political affiliation's impact is explained by the diversion of resources and their inefficient use since they have been attained from corruption and favoritism.…”
Section: Political Experiencementioning
confidence: 95%
See 1 more Smart Citation
“…A high level of heterogeneity was found in a study conducted by Sharif and Rashid (2014) where particular board composition variables were examined in the light of CSR quantity and quality. From agency theory perspective, Leong et al (2015) found an impact of board composition on firm's performance and reporting. Significant influence of different board attributes on CSR is evidenced by several studies (Huang, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…13, No. 5; 2018 26 the internal auditors (Leong, Paramasivam, Sundarasen, & Rajagopalan, 2015). The possibility of attributing the functions of the supervisory body to the board of statutory auditors has been stated; wherever the choice is to maintain a distinction between the two bodies, the college has to obtain the information relating to the organizational model adopted by the company from the supervisory body.…”
mentioning
confidence: 99%